Why/Why Not. - Ronk, Martha (New California poetry., 2003)
Why/Why Not presents a speaker caught in quandaries created by changing perspectives, fervors, and locales. Why do we act one way here and another there; why can't a mind stay made up; why do we hate and love at the same time; why does memory fade or insist; why does the ordinary seem so uncanny? These questions are captured in lines that collide and merge, in irreverent and offhand jibes, and in plaintive repetitions. Why/Why Not moves across a vivid terrain--the stage of Hamlet, Phillip Marlowe's Los Angeles, Prague, paintings and gardens--to push through a tangle of ways to make sense of the w.